Tax Morale Determinants of Self – Employed Taxpayers: A Case Study on Online Taxi Driver in Bandung Regency - Restiawati, Evi; Sari, Diana (Journal of Accounting and Finance Management, 2025)
Indonesia’s tax ratio has experienced significant fluctuations, declining from 9.76% in 2019 to 8.33% in 2020 due to the COVID-19 pandemic, before increasing again in 2021 and 2022. However, in 2023, the tax ratio fell once more as commodity prices were not as favorable as the previous year. According to the IMF, Indonesia has had the lowest tax ratio in ASEAN since 2018. The target tax ratio for 2024 is set between 10.09% and 10.29% of GDP, lower than the 2023 achievement of 10.31%. Increasing voluntary tax compliance among informal sector workers is considered crucial to achieving a higher tax ratio. Tax morale plays a vital role in enhancing voluntary taxpayer compliance. This study aims to examine the effect of tax rate, tax fairness perception, financial constraints, tax audits, and religiosity on the tax morale of individual taxpayers in Bandung City/Regency. A quantitative approach was employed through a survey method involving 384 respondents. Data analysis was conducted using multiple linear regression. The results show that tax rates, tax fairness perception, tax audits, and religiosity have a significant positive effect on tax morale, while financial constraints have no significant effect. These findings indicate that improving tax morale can be encouraged through fair fiscal policies, accountable tax audit implementation, and the strengthening of moral and religious values within society.